2001
DOI: 10.1093/clinchem/47.5.858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the TAS Analyzer and the Low-Range Heparin Management Test in Patients Undergoing Extracorporeal Membrane Oxygenation

Abstract: Background: The new Low-Range Heparin Management Test (LHMT), a method for point-of-care testing (POCT) of heparinization, has been designed to function at the low to moderate heparin concentrations typically found in patients undergoing extracorporeal membrane oxygenation (ECMO). In this study, the new method is compared with two POCT methods and a laboratory-based anti-Xa assay. Methods: We obtained 760 whole blood samples from 13 patients undergoing ECMO. All samples were tested immediately b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…11 On the other hand, no correlation had been reported for low concentrations of anticoagulation between Hemochron Ò Jr ACT-LR values and anti-Xa activity during ECMO. 19 Our different results could be explained by physiological factors during ECMO, such as intense coagulopathy, hypothermia and haemodilution. This study confirms that low anti-Xa activity is the most appropriate setting for Hemochron Ò Jr II Signature device with low-range cartridges.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…11 On the other hand, no correlation had been reported for low concentrations of anticoagulation between Hemochron Ò Jr ACT-LR values and anti-Xa activity during ECMO. 19 Our different results could be explained by physiological factors during ECMO, such as intense coagulopathy, hypothermia and haemodilution. This study confirms that low anti-Xa activity is the most appropriate setting for Hemochron Ò Jr II Signature device with low-range cartridges.…”
Section: Discussionmentioning
confidence: 77%
“…ACT-LR has already been compared with laboratory-based anti-Xa activity in patients undergoing extracorporeal membrane oxygenation (ECMO). 19 Several factors involved in the relationship between ACT and laboratory assay could explain the poor correlation found.…”
mentioning
confidence: 99%
“…Although ACTs remain the standard of care for anticoagulation monitoring during ECLS (98%), new data suggest other methods may be more valuable for measuring systemic anticoagulation over long periods of time (25), such as thrombin generation and heparin levels via anti-Xa activity. Studies have shown that ACTs do not correlate with thrombin generation in the pediatric population, possibly because of increased hemodilution and lower fibrinogen levels compared with the adult population.…”
Section: Anticoagulationmentioning
confidence: 99%
“…The target ACT varies with technique and patient characteristics. 62,63 For renal replacement therapy, the goal of anticoagulant therapy is to limit filter and circuit clotting. To accomplish this, an ACT of 170–220 seconds has been recommended.…”
Section: Monitoring For Anticoagulation Of Extracorporeal Circuitsmentioning
confidence: 99%